Pengaruh Cashback Dan Promosi Langsung E-Wallet Terhadap Keputusan Pengeluaran Generasi Z di Kota Bengkulu - Nayla Julia; Safitri, Nazwa Okta; Rahmadanisa, Naailah; Isnaini, Cahaya Sukma ; Manulang, Lasro ; Akbar, Muhammad Danial; Erzyanda, Gio (Student Journal of Business and Management, 2026)
This study aims to analyze the effect of Cashback and direct E-Wallet promotions, including discounts and flash sales, on the spending decisions of Generation Z in Bengkulu City. The study utilized a quantitative method with purposive sampling, engaging 150 respondents aged 17–28 who are active E-Wallet users. Data were gathered באמצעות a Likert-scale questionnaire and processed using IBM SPSS Statistics version 31.0.2.0. The analytical procedures included validity and reliability testing, classical assumption checks, multiple linear regression analysis, and hypothesis testing through t-tests and F-tests. The results indicate that partially, Cashback does not have a significant effect on Generation Z’s spending decisions, while direct E-Wallet promotions have a significant effect. Simultaneously, Cashback and direct E-Wallet promotions have a significant influence on spending decisions, contributing 53.9%, while the remaining variance is explained by other factors outside this study. These findings highlight that digital promotion strategies based on E-Wallets, particularly direct promotional programs such as discounts and flash sales, play an important role in shaping the consumptive behavior of Generation Z and should be prioritized in the digital marketing strategies of E-Wallet service providers.